Carrier based PWM of hybrid 5-level inverter with open-end winding three- phase load - Nguyen, Ngoc Ho; Nguyen, Van Nho (Journal of Technical Education Science, 2010)
This paper presents a simple carrier based PWM technique to control a hybrid multilevel inverter. A conventional 3-level NPC inverter and 2-level inverter are connected in series to supply an open-end winding three phase load. Proposed PWM method is then verified in steady state and dynamic transient phenomena using MATLAB simulation program.